2011
DOI: 10.2174/157016211797635973
|View full text |Cite
|
Sign up to set email alerts
|

Womens Desire for Children in an HIV Population: A Clinical Pilot Study in Burkina Faso

Abstract: Even if the results of this pilot study are preliminary, they show that HIV positive and negative women have a relatively similar desire for children, even though seropositive women seem to want fewer children than their uninfected counterparts. Most of the reasons which reduce HIV positive women's desire to have children are directly linked to HIV. This is why getting these women informed about materno-fetal transmission risks and existing treatments is really important to give them the opportunity to make a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The only study we identified of HIV-infected African women with a level of childbearing intention similar to our findings was from Burkina Faso and reported as an intention proportion of 70% (Lemoine et al, 2011). The high proportion of childbearing intention among our HIV-infected participants may be related to the young age of our cohort.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The only study we identified of HIV-infected African women with a level of childbearing intention similar to our findings was from Burkina Faso and reported as an intention proportion of 70% (Lemoine et al, 2011). The high proportion of childbearing intention among our HIV-infected participants may be related to the young age of our cohort.…”
Section: Discussionsupporting
confidence: 83%
“…While several studies have found younger age to be associated with increased childbearing intention (Asfaw and Gashe, 2014; Haddad et al, 2016; Kawale et al, 2014; Lemoine et al, 2011), some have identified increased age as a positive predictor of childbearing intention (Gyimah et al, 2015; Laar et al, 2015). A meta-analysis of fertility desires among HIV-infected men and women identified age less than 30 to be strongly associated with fertility intention (Berhan and Berhan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Age less than or equal to 35 years-old was associated with increased odds of desire for a child, and this age-related finding has been consistently documented (Caroline, et al, 2011; Taulo et al, 2009; Wagner, et al, 2012). Not yet having children was associated with increased odds of fertility desire, a finding well-supported by similar studies in the region (Kipp, et al, 2011; Schwartz, et al, 2012; Taulo, et al, 2009).…”
Section: Discussionmentioning
confidence: 75%
“…Research from sub-Saharan Africa suggests that the desire for children in the era of ART ranges from 45-75% (Caroline et al, 2011; Cooper et al, 2009; Schwartz et al, 2012). Despite data suggesting people with HIV desire children, most programs have focused on integrating contraception and ART delivery, but have not developed programs to specifically address fertility desires and safer conception.…”
Section: Introductionmentioning
confidence: 99%
“…Malawi is no exception when it comes to the high value placed on motherhood even among women living with HIV. Findings of prior studies conducted in sub-Saharan Africa suggest that the desire to have children, especially since the advent of ART, ranges from 45 to 75% [ 16 , 17 ]. Several factors have been identified as influencing the women’s desire for pregnancy and childbearing.…”
Section: Introductionmentioning
confidence: 99%